DOMINASI BUDAYA PADA KELUARGA PERKAWINAN CAMPUR ANTAR ETNIS - Saputri, Febrianti; Bahari, Yohanes; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis title is "Cultural Dominance At Inter-Ethnic Mixed Marriage Family". The purpose of this study was to determine the cultural dominance of ethnic intermarriage families in the hamlet of Paradise. The approach used is qualitative descriptive method. The data collection technique used is the technique of interview, observation and documentation. The analysis in this study are presented in descriptive qualitative by using informants as many as 10 people consisting of 5 pairs of ethnic intermarriage-Dayak Java, Java-Sambas, and Java-Bugis. The results showed that there has been a cultural domination kinship systems related to culture, livelihood systems, language, and art on each pair of mixed marriages. Some informants have dominated in his work, from the kinship system of each child to follow the ethnic intermarriage couples ayahya, customary marriages performed depends on the agreement of the mixed marriage couples. 4 languages in terms of interbreeding dominant partner uses the Java language, while one pair of intermarrying more dominant use Malay Sambas. In terms of art, intermarried couples retain the more dominant Javanese art. while one pair of intermarrying more dominant use Malay Sambas. In terms of art, intermarried couples retain the more dominant Javanese art. while one pair of intermarrying more dominant use Malay Sambas. In terms of art, intermarried couples retain the more dominant Javanese art.Keywords: Cultural Domination, Inter-Ethnic Marriages